Peran Viral Marketing dan Electronic Word of Mouth (E-WOM) dalam Membentuk Minat Beli Konsumen Pizza Miukara di Kota Tebing Tinggi - Ekawati, Yuni Andri; Aini, Fuji Asih; Dwinov, Tania (STIE Bina Karya, 2025)
This study aims to determine the influence of the role of Vital Marketing, and Electronic Word of Mouth (E-WOM) in shaping the Purchase Interest of Miukara Pizza Consumers in Tebing Tinggi City. This study uses a quantitative research method. The number of samples in this study was 85 respondents using purposive sampling techniques. The test tool used was the Statistical Program of Social Science (SPSS) version 26 for Windows software. The results of this study concluded that the role of Vital Marketing, and Electronic Word of Mouth (E-WOM) had a positive and significant influence in shaping the Purchase Interest of Miukara Pizza Consumers in Tebing Tinggi City.